Social Media in the Anticorruption Movement: Social Network Analysis on the Refusal of the “Koruptor Boleh Nyaleg” Decision on Twitter - Zempi, Chairun Nisa; Rahayu, Rahayu (UI Scholars Hub, 2019)
This article aims to reveal the social network of an anticorruption movement via social media by showing the key actors, exchange of messages, and dynamics of the inter-temporal communication network. The anticorruption movement seems to be developing in line with increasing public awareness and the support of information and communications technology. By applying social network analysis on Twitter with the hashtag #koruptorkoknyaleg, study results indicated that a social network was formed in order to facilitate public voices pertaining to the issue of corruption. Actors possessing a track record in fighting against corruption in Indonesia became pioneers in establishing a social network. The research findings also indicated that the social network structure was dynamic. Although the social network seems to facilitate the spread of the anticorruption movement, it has limitations in altering political decisions relating to cases of corruption.